Antimicrobial activity of Phomopsis sp. ED2, an endophytic fungus isolated from Orthosiphon stamineus Benth - Tong Woei Yenn; Darah Ibrahim; Latiffah Zakaria (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This study aimed to investigate the antimicrobial activity of the endophytic fungus Phomopsis sp. ED2, which was previously isolated from the flower of the medicinal plant Orthosiphon stamineus Benth, in Penang, Malaysia. The 14 days-old fungal cultures were extracted with different organic solvents, include hexane, dichloromethane, ethyl acetate and butanol. The antimicrobial activities of the extracts were tested by disc diffusion assay. Based on the results, most antimicrobial compounds were present in the ethyl acetate fraction, and this extract could significantly inhibit the activity of bacteria, yeasts and fungi. The results also indicate that the antimicrobial compounds were mainly associated with the fungal biomass and all the Gram-positive test bacteria were inhibited by the ethyl acetate extract of the fungal biomass. Notably, methicillin-resistant Staphylococcus aereus exhibited a high sensitivity to the extract, with a low minimal inhibitory concentration and low minimal lethal concentration. The isolate also effectively inhibited the growth of the dermatophytes Microsporum gypseum and Trichophyton rubrum. Preliminary phytochemical screening also demonstrated that the extract contains phenols and steroids which possess antimicrobial activity. These results reveal that the endophytic fungus Phomopsis sp. is potential source of novel chemotherapeutic agents